Menghindari Terjadinya Sengketa Ahli Warits dalam Keluarga Muslim Indonesia - Muhammad Amanuddin (Publikasi Indonesia, 2022)
This objective is to provide a solution so that disputes over warrants in the family can be avoided or at the very least, can be minimized, because every human being will eventually leave this world forever. When a person leaves forever, all of his property, both rights and obligations, will be directly inherited by the warits or his family. One source of disputes in family life is warits property, sometimes in a family that was once united then divorced is the issue of disproportionate distribution of inheritance in accordance with applicable law. Lack of knowledge about the science related to warits, is one of the causes of warits disputes, in addition to the lack of socialization about the importance of the distribution of warits property when the owner of the property has died, the reluctance of the warits to share the existing warits property, whether because of ignorance or because of shyness with people or the surrounding community. The solution that the author offers, among others, is to increase the volume and target of socialization about the importance of the division of warits property when a person has died, in addition to the need to record warits property, and last but not least, it is necessary to legalize it in the Islamic family legislation in Indonesia in order to benefit the community.